African Walnuts (Tetracarpidium conophorum) Modulate Hepatic Lipid Accumulation in Obesity via Reciprocal Actions on HMG-CoA Reductase and Paraoxonase - Uti, Daniel E.; Atangwho, Item J.; Eyong, Eyong U.; Umoru, Grace U.; Egbung, Godwin E.; Rotimi, Solomon O.; Nna, Victor U. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Background: Obesity is characterized by increased body fat and involves an imbalance between the synthesis and degradation of lipids. Objective: The study aimed to investigate the effect of African walnuts (Tetracarpidium conophorum) on lipids storage and the regulatory enzymes of hepatic lipid metabolism in obese rats. Methods: Nuts were extracted in ethanol (WE) and further separated to obtain the ethyl-acetate fraction (ET) and the residue (RES). These were administered orally to 3 groups of monosodium glutamate- obese rats (n = 6), respectively, for 6 weeks. Other groups in the study were: normal (NC), obese control (OC) and standard control (SC) which received orlistat. Hepatic total lipids, total phospholipids, triacylglycerol (TG), total cholesterol (TCHOL), 3-hydroxyl-3-methylglutaryl-CoA (HMG-CoA) reductase and paraoxonase were studied. Results: Total lipids, TG and TCHOL which increased in OC compared to NC group, decreased. HMG-CoA reductase activity decreased in the 3 study groups relative to OC. Paraoxonase activity which decreased in OC was up-regulated, while the magnitude of hepatic cholesterol decreased from 94.32 % in OC to 52.19, 65.43 and 47.04 % with WE, ET and RES, respectively. Flavonoids, alkaloids, glycosides, tannins and saponins were detected in the nut. GC-MS analysis revealed 16, 18 and 10 volatile components in WE, ET and RES, respectively. Unsaturated fatty acids (linolenic acids: 33.33, 47.95 and 50.93 %, and α-linolenic acids: 25, 19.66 and 26.63 %) in WE, ET and RES, respectively, are the most abundant, and likely to be responsible for the observed activity. Conclusion: African walnuts can prevent hepatic lipid accumulation through reciprocal actions on HMG-CoA reductase and paraoxonase in obesity.
Keywords: HMG-CoA reductase